Seed Oil Quality and Cultivation of Sambucus williamsii Hance as a New Oil Crop - Wang, Shuyue; Yu, Yongxin; Cui, Mingxiao; Liu, Kehai; Liu, Kewu (Frontiers in Nutrition, 2021)
Natural edible oil derived from wild non-cultivated oil crops contributed to human daily nutritional diversity and disease prevention. It was important to investigate the nutritional value of these oils and the feasibility of crop cultivation. The present study focused on the assessment of seed oil quality of Sambucus williamsii Hance (SWH) and its molecular breeding. Wild Sambucus williamsii Hance (SWH) seed oil was extracted by supercritical CO2 technology and the composition of the oil was determined by GC-MS analysis. The oil content of SWH seeds reaches around 40%. And its seed oil was found to be rich in unsaturated fatty acids, including 24.24% of linolenic acid and 50.56% of linoleic acid, and vitamin E (25.92 mg kg-1). The cytotoxicity and heavy metal analysis showed SWH seed oil was safe for consumption. Also, the SWH strains with excellent characteristics were screened out for cultivation according to genetic diversity and morphological analysis. Amplified fragment length polymorphism (AFLP) markers were used to evaluate the genetic diversity of 28 accessions of wild SWH seeds and 5 accessions were selected to cultivate. Among them, two strains of SWH (sample 3 and 6) with high yielding (275.7 and 266.8 area yield kg-1) were suitable for dense planting and could be used to establish the raw material forest of SWH seed oil. The results of this study indicated the potential of development of selected SWH as novel oil crops and their wide cultivation.